Effect of selected mycorrhizal strains and six soil series on phosphorus availability in South-Western Nigeria - Adebimpe Adebukola Aboderin; Gbade Oyewumi Oyediran (Talenta Publisher, 2026)
The availability of soil phosphorus is a major constraint to crop production. This could be ameliorated by mycorrhizal inoculation. This study assessed the effect of selected mycorrhizal strains and soil series on phosphorus availability in South-Western Nigeria. The study was conducted at the Teaching and Research Farm, Ladoke Akintola University of Technology, Ogbomoso, Oyo State, Nigeria. The two factors tested in the pot trials were four treatment levels, including: no mycorrhizal inoculation (control), and inoculation with Glomus mosseae, Glomus clarum, and Glomus fasculatum, respectively, and six soil series (Iwo, Apomu, Itagunmodi, Araromi, Egbeda, and Gambari series) collected from different locations in South-Western Nigeria. The experimental design was factorial, arranged in a randomized complete block design with three replications. Phosphorus (P) uptake was determined from the plant after harvesting. Root infectivity was determined by the grid line intersects method. Data were analyzed using SAS at P ≤ 0.05, and means were separated using the Least Significant Difference. Results showed that the Apomu series with Glomus fasculatum produced the highest mycorrhizal infectivity (57.42%). The highest P uptake of 5.33 g/plant was obtained from the Iwo series with Glomus fasculatum.